NSCA's essentials of sport science (Human Kinetics, 2022)
Within the domain of sport, the application of science is more apparent than ever before. Not only are universities and academic institutions scientifically investigating sport as one element of human performance, but professional teams, sporting organizations, and private training companies are embracing approaches that use scientific principles to help their athletes and teams gain a competitive edge in sporting competition.